2020
DOI: 10.21608/ajbas.2019.18950.1002
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Co3O4 nanoparticles from amino acids mixed ligands and its adsorption properties

Abstract: The metal precursor derived from the reaction of Co(II) acetate with the mixed ligands of lysine(Lys) and glutamine(Glu) was used to synthesize Co 3 O 4 nanoparticles. The precursor was characterized by (C, H, N, M), IR, electronic spectra, TGA and effective magnetic moments. Co 3 O 4 nanoparticles were prepared from calcinations of the synthesized precursor at 800 o C. The obtained nanoparticles were characterized by X-ray powder diffraction and transmittance electron microscope. The average particle size is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(43 reference statements)
0
0
0
Order By: Relevance
“…[18][19][20][21] These elements' compounds are helpful in other domains, especially nano fields. [22][23][24][25][26] In literature, the Schiff bases (ligands) produced from 2-hydroxy acetophenone and primary amine (-NH2) compounds are highly remarkable due to their non-toxic qualities, aqueous solubility, excellent coordinating ability, and metabolic activity. [27][28][29] It has been demonstrated that such similar ligands coordinate with a wide range of ionized bivalent metals, including Fe 2+ , Co 2+ , Cu 2+ , Ni 2+ , and Zn 2+ ; these complexes have been demonstrated to contribute to medication-proof against malignancy in vivo and in vitro cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21] These elements' compounds are helpful in other domains, especially nano fields. [22][23][24][25][26] In literature, the Schiff bases (ligands) produced from 2-hydroxy acetophenone and primary amine (-NH2) compounds are highly remarkable due to their non-toxic qualities, aqueous solubility, excellent coordinating ability, and metabolic activity. [27][28][29] It has been demonstrated that such similar ligands coordinate with a wide range of ionized bivalent metals, including Fe 2+ , Co 2+ , Cu 2+ , Ni 2+ , and Zn 2+ ; these complexes have been demonstrated to contribute to medication-proof against malignancy in vivo and in vitro cells.…”
Section: Introductionmentioning
confidence: 99%
“…These ions produce small molecular mass complexes more effective than various ailments 18–21 . These elements' compounds are helpful in other domains, especially nano fields 22–26 …”
Section: Introductionmentioning
confidence: 99%